Collaborative order management: toward standard solutions for interorganisational order management. (31st March 2005) - Alt, Rainer; Gizanis, Dimitrios; Legner, Christine
Order management ranks among the key operational processes. Inefficiencies within this process have direct impacts on customer service, order cycle times as well as order execution costs. The massive investments in implementing systems for enterprise resource planning (ERP) have already led to significant improvements in managing orders across organisational units within enterprises. However, ERP systems have not been designed for exchanging order information with business partners. Established interorganisational solutions such as electronic data interchange (EDI) are not widespread and existing solutions are largely proprietary. This article discusses the emerging standard solutions and services for interorganisational or collaborative order management (COM). Starting from a generic definition of the COM process, an explorative study aims to provide an overview on the status, developments and perspectives of COM. Order management solutions and electronic services are discussed as the two main emerging areas in COM and various providers are analysed using content analysis and case research. The current picture shows fragmented solutions and a substantial need for integration. Possible scenarios and open research questions are provided in the concluding section of this paper.